CURRENT STATE OF COMPUTERIZATION OF EDUCATION - Vetchanin, Yevhen (Educological discourse, 2018)
The article reviews the process of computerization of education, analyzes computer technologies used in teaching and shows possible problems that may arise during the implementation of these technologies. This article shows that the use of different computer technologies in education expands the capabilities of teachers and students. Computerization has a positive effect on the learning process and allows to diversify it. The author highlights the use of network technologies, multimedia technologies and virtual reality technologies. Multimedia technologies allow using video and audio materials during the lesson and creating multimedia presentations. Their use saves time while preparing for the lesson and during it, provides the possibility of editing information in real time and the opportunity to illustrate the educational material. Network technologies allow accessing information concentrating points, exchanging messages via e-mail or the communication software and it can be used to distribute the load between computers in large projects, for shared usage of technical resources and for remote control. The use of virtual reality technologies opens up many new opportunities in education and has such benefits as visibility, security, interactivity and focusing. VR technology greatly enhances the informativity of the lesson material, thereby enhancing the motivation and interest of students and the effectiveness of their learning. The article also analyzes the use and impact of computer technologies on distance learning